2009
DOI: 10.1002/ejsp.657
|View full text |Cite
|
Sign up to set email alerts
|

Justice through consensus: Shared identity and the preference for a restorative notion of justice

Abstract: We propose a concept of restorative justice as a sense of justice deriving from consensus about, and the reaffirmation of, values violated by an offence (in contrast to punishment-based retributive justice). Victims should be more likely to seek restorative justice (and less likely retributive justice) when they perceive to share a relevant identity with the offender. In Study 1, when the relevant identity (university affiliation) shared with the offender was made salient (vs. not), participants found a consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 57 publications
1
89
2
Order By: Relevance
“…For example, the perceived prototypicality (Vidmar, 2002) or moral disposition of the offender (e.g. Hollander, 1958), as well as the extent to which the victim shares a social identity with the offender (Okimoto et al, in press;Wenzel et al, 2008) or defines the self through his or her membership in the relevant group (Wenzel & Thielmann, 2006), may have important implications for the strength of the victim's concern for value consensus. Likewise, the preferred route towards consensus may be determined by various situational cues or personality factors, such as high authoritarianism (Feather, 1998(Feather, , 2002Tyler & Webber, 1983) or social dominance (Sidanius, Pratto, van Laar, & Levin, 2004) which would theoretically lead to less focus on values and more concern over the interpersonal status and power lost in the transgression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the perceived prototypicality (Vidmar, 2002) or moral disposition of the offender (e.g. Hollander, 1958), as well as the extent to which the victim shares a social identity with the offender (Okimoto et al, in press;Wenzel et al, 2008) or defines the self through his or her membership in the relevant group (Wenzel & Thielmann, 2006), may have important implications for the strength of the victim's concern for value consensus. Likewise, the preferred route towards consensus may be determined by various situational cues or personality factors, such as high authoritarianism (Feather, 1998(Feather, , 2002Tyler & Webber, 1983) or social dominance (Sidanius, Pratto, van Laar, & Levin, 2004) which would theoretically lead to less focus on values and more concern over the interpersonal status and power lost in the transgression.…”
Section: Discussionmentioning
confidence: 99%
“…Restorative practices involve the affected parties dealing with the injustice through interaction and mutual understanding, focusing on restoring a sense of justice through renewed value consensus (Wenzel et al, in press). Recent empirical work has shown that heightened value concerns are related to greater endorsement of both traditional punishments and restorative processes (Wenzel & Thielmann, 2006;Wenzel et al, 2008), suggesting that both restorative and retributive processes may help consensualise values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lawsuits between patients and the hospital). Staying within the context of legal disputes, apologies are an integral part of restorative justice (Wenzel, Okimoto, Feather, Platow, 2010;Strang et al, 2006). Indeed, restorative justice conferences in which a victim and perpetrator meet has been shown to benefit greatly from an apology (Strang, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Transgression victims prefer the use of restorative procedures to more punitive approaches when they share an identity with the offender and/or desire to establish consensus about the violated value (e.g., Wenzel et al 2012;Wenzel et al 2008Wenzel et al , 2010. And, people have lessened negative emotional experiences and calmer physiological reactions with restorative, as compared to retributive, responses to imagined transgressions against them (Witvliet et al 2008).…”
Section: Restorative Justice and Its Benefits For Victimsmentioning
confidence: 99%